2017
DOI: 10.1017/s0021859617000405
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations in evapotranspiration and net water requirements of typical Mediterranean crops on the island of Cyprus

Abstract: SUMMARYDiminishing irrigation water availability and increased crop evapotranspiration (ET) have already been shown to pose threats to agricultural productivity. The aim of the current study was to estimate the values and trends of both ET and net irrigation requirements (NIR) of those crops consuming most water due to the size of their cultivated area (citrus and potatoes) in a water-scarce region with typical Mediterranean climate, such as Cyprus, analyse possible spatial and temporal variations of these par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…However, adverse climatic conditions and lack of adequate soil moisture causing failures during transplanting led to an abandonment of crops [36]. Locally, irrigation requirements are calculated based on a Class A evaporation-pan methodology adopted from Cyprus Agricultural Research Institute [37] following Allen et al [38]. For example, the mean yearly evapotranspiration rate (i.e., crop water requirements) for high water-demanding crops such as bananas is estimated at 1255 mm, for citrus it is 846 mm and for olive trees (which is considered a low water-demanding crop) it is 430 mm.…”
Section: Study Areamentioning
confidence: 99%
“…However, adverse climatic conditions and lack of adequate soil moisture causing failures during transplanting led to an abandonment of crops [36]. Locally, irrigation requirements are calculated based on a Class A evaporation-pan methodology adopted from Cyprus Agricultural Research Institute [37] following Allen et al [38]. For example, the mean yearly evapotranspiration rate (i.e., crop water requirements) for high water-demanding crops such as bananas is estimated at 1255 mm, for citrus it is 846 mm and for olive trees (which is considered a low water-demanding crop) it is 430 mm.…”
Section: Study Areamentioning
confidence: 99%
“…Due to the extremely high soil water content, the depositional zones need to be controlled with plants that minimize the intensity of gully erosion, soil cracks, landslides, and soil creeps [55]. The high water content can be maintained by cultivating high water consumption plants such as bamboo [56][57][58], banana [59,60], sugar palm [61,62], and coconut [63]. They can be planted at the lowest elevation of the depositional zone and can be combined with the recommended crop choices for erosional zones.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the pan A coefficient, a constant value of 0.79 provides a good estimation of reference evapotranspiration (ET O ) rates in plastic greenhouses under Mediterranean conditions [119], while Çakir et al [57], working with cucumber in a solar greenhouse covered with netting material, indicated a plant-pan coefficient between 1.25 to 1.50. In line with this, for several crops in Cyprus, the evapotranspiration rate was calculated from reference evapotranspiration based on pan evaporation data, following the methodology proposed by Allen et al [118] as indicated in Table 3 derived from Markou and Papadavid and Christou et al [120,121]: Table 3. Monthly and yearly estimated evapotranspiration requirements for several crops in protected cultivation (mm).…”
Section: Crop Evapotranspiration and The Water Balance Methodsmentioning
confidence: 99%